OPTIMIZATIONS OF DEEP LEARNING OBJECTS DETECTION MODELS FOR INFERENCE ACCELERATION ON GENERAL-PURPOSE AND HARDWARE-ACCELERATED SINGLE-BOARD PLATFORMS - Dmytro Myroniuk; Bohdan Blahitko (Електроніка та інформаційні технології)
Background. Description and preparation of modern approaches for deep learning object detection models are provided. Deep learning frameworks for model training and inference, such as TensorFlow and TensorFlow Lite, are used as bases. The concepts of deep learning model optimization are analyzed.